Você está na página 1de 178

 

ε

 

  ε  

F x , F a F m x
F x , F a
F
m
x

m dx 2 F − F a − F x = dt 2 , c
m dx 2
F − F a − F x
=
dt 2 ,
c dx
F a
=
dt ,
F x
=
kx,
F = m dx 2
+ c dx dt + kx.
dt 2

x (0) = 0 x˙ (0) = 0 x x t
x (0) = 0 x˙ (0) = 0
x
x
t

a d
a d

a d

a d x (k) k

x (0)

=

x (k + 1)

=

,

0 0, x (k) + 1 u = a x (k) 1 u = d x (k) 1

= x ( k + 1) = , 0 0 , x ( k ) +

x (k)

5 4 3 2 1 k 0 1 2 3 4 5 6 7 8
5
4
3
2
1
k
0
1
2
3
4
5
6
7
8

×

×

        u ( t ) y ( t )  

        u ( t ) y ( t )  

 
     
   
 
 

u (t)

u ( t ) y ( t )
u ( t ) y ( t )

u ( t ) y ( t )
u ( t ) y ( t )

y (t)

 
 

        u ( t ) y ( t )  

5 4 3 2 1 a a a d a a a d
5
4
3
2
1
a
a
a
d
a
a
a
d

5 4 3 2 1 a a a d a a a d

a d

5 4 3 2 1 a a a d a a a d
5
4
3
2
1
a
a
a
d
a
a
a
d

aaadaaad

5

4

3

2

1

aaadaaad 5 4 3 2 1 a a a d a a a d
aaadaaad 5 4 3 2 1 a a a d a a a d

a

a

a

d

a

a

a

d
d

d d

5

4

3

2

1

d d 5 4 3 2 1 a a a d a a a d
d d 5 4 3 2 1 a a a d a a a d

a

a

a

d

a

a

a

d
d

daa d

5

4

3

2

1

daa d 5 4 3 2 1 a a a d a a a d
daa d 5 4 3 2 1 a a a d a a a d

a

a

a

d

a

a

a

d
d

(a, t 0 ) (a, t 1 ) (a, t 2 ) (d, t 3 ) (a, t 4 ) (a, t 5 ) (a, t 6 ) (d, t 7 )

5

4

3

2

1

1 ) ( a, t 2 ) ( d, t 3 ) ( a, t 4
1 ) ( a, t 2 ) ( d, t 3 ) ( a, t 4

a

a

a

d

a

a

a

d
d

b a a 0 1 2 a b
b
a
a
0
1
2
a b
0 1 2
0
1
2

b a a 0 1 2 a b 0 1 2

b

0 1 2
0
1
2
a a 0 1 2 a b
a
a
0
1
2
a b

b 0 1 2 a a 0 1 2 a b

b a a 0 1 2 a b
b
a
a
0
1
2
a b
0 1 2
0
1
2

b a a 0 1 2 a b 0 1 2

0 f (0, a) = 1 f (0, b) = 2 aa b

b

a a 0 1 2 a b
a
a
0
1
2
a b
 
0
0

1
1
2
2

0 f (0 , a ) = 1 f (0 , b ) = 2 aa

G = (X, E, f, Γ, x 0 , X m )

X

E

f

f :

X × E X

Γ Γ : X 2 E

x 0

X m

x 0 X X m X

2 E E

→ X Γ Γ : X → 2 E x 0 X m x 0 ∈

2 E

E E 2 E E

2 E = {x : x E} .

E P (E)

2 E E E 2 E E 2 E = { x : x ⊆ E

2 E

E = {a, b, g} E

2 E = {∅, {a} , {b} , {g} , {a, b} , {a, g} , {b, g} , {a, b, g}} .

E 2 n n E 2 E

{ b } , { g } , { a, b } , { a, g

X = {x, y, z}

E = {a, b, g} a b a x y g a, g z
E = {a, b, g}
a
b
a
x
y
g
a, g
z

b

X = { x, y, z } E = {a, b, g} a b a x

x

f (x, a) = x, f (x, g) = z, a b a x y
f (x, a) = x,
f (x, g) = z,
a
b
a
x
y
g
a, g
z

b

x f (x, a) = x, f (x, g) = z, a b a x y

f (y, a) = x, f (y, b) = y, y a b a x
f (y, a) = x,
f (y, b) = y,
y
a
b
a
x
y
g
a, g
z
b

f (z, a) = y,

f (z, b) = z,

z

a b a x y g a, g z
a
b
a
x
y
g
a, g
z

b

f (z, g) = y,

f ( z, a ) = y, f ( z, b ) = z, z a

Γ (x)

Γ (y)

Γ (z)

=

=

=

a

{a, g} ,

{a, b} ,

{a, b, g} ,

a

b

Γ ( x ) Γ ( y ) Γ ( z ) = = = a
x
x
y
y
Γ ( x ) Γ ( y ) Γ ( z ) = = = a

a, g

g z
g
z

b

Γ ( x ) Γ ( y ) Γ ( z ) = = = a

x 0 = x

X m = {x, z}

a b a x y g a, g z
a
b
a
x
y
g
a, g
z

b

x 0 = x X m = { x, z } a b a x y

X × E

X × E Γ (x) = E, x X

a b a x y g a, g z
a
b
a
x
y
g
a, g
z

b

X × E X × E Γ ( x ) = E, ∀ x ∈ X

a b a x y g a, g z
a
b
a
x
y
g
a, g
z

b

a b a x y g a, g z b

G L (G) G L (G) G a b a x y g a, g
G
L (G)
G L (G) G
a
b
a
x
y
g
a, g
z
b

E = {a, b, g} aag ∈ L (G) bag ∈/ L (G) a b
E = {a, b, g}
aag ∈ L (G) bag ∈/ L (G)
a
b
a
x
y
g
a, g
z
b

s E

E = {a, b, g} E s 1 = a s 2 = aaa s 3 = gba s 4 = bb

s E E = { a, b, g } E s 1 = a s 2

u v w s = uvw s u

s u, v, w

s w

E = {a, b, g} s = abga ε a ab abg abga ε a ga bga abga bg

w E = { a, b, g } s = abga ε a ab abg abga

L E E

ε 1

s = εs = s

εε = ε

ε

L E E ε 1 s sε = εs = s εε = ε ε

E = {a, b, g} E

L 1 = {ε, a, abb}

L 2 = { ε a }

L 2 = {abg, aaa, abb, agg,

L 2 = {a} × {a, b, g} × {a, b, g}

.}

ε a } L 2 = { abg, aaa, abb, agg, L 2 = { a

E = {a, b, g} L 3 = { a }

L 3 = {a}∪ {a}× {a, b, g}∪ {a}× {a, b, g} 2

∪ {a}× {a, b, g} n

{ a } L 3 = { a }∪ { a }× { a, b, g

E = {a, b, g} L 3 = { a } G 3 L 3
E = {a, b, g} L 3 = {
a } G 3
L 3 L m (G 3 ) = L 3
G 3
G 3 :
a, b, g
a
0
1

E = {a, b, g} L 3 = { a } G 3 L 3 L

L m (G 3 ) ⊆ L (G 3 )

ε ε ∈ L (G 3 ) ε / L m (G 3 )

G 3 : a, b, g a 0 1
G 3 :
a, b, g
a
0
1

E = {a, b, g} a

E = { a, b, g } a

E E n n E

E = {a, b, g} E 5

E 5 = {aaaaa, aaaab, aaaag, aaaba,

3 5

.} = E × E × E × E × E,

2 E E n

E 5 = { aaaaa, aaaab, aaaag, aaaba, 3 5 . } = E × E

E E

E {ε} ∪ E + ,

E + = E E 2 E 3

L E L E . s E s E

E + = E ∪ E 2 ∪ E 3 ∪ L E L ⊆ E

E = {a, b, g} E

E = {ε, a, b, g, aa, bb, gg, ab, ag, bg, gb, abg,

, abgaag,

.}

E = { a, b, g } E E ∗ = { ε, a, b, g,

L 1 L 2 E L 1 L 2

L 1 L 2 = {s : s = uv, u L 1 , v L 2 } .

L 1 = {aa, bb, gg} L 2 = {a, g} E = {a, b, g}

L 1 L 2 = {aaa, aag, bba, bbg, gga, ggg} .

aa, bb, gg } L 2 = { a, g } E = { a, b,

L E L L L = {s ∈ E ∗ : ∃t ∈ E ∗
L E L L
L = {s ∈ E ∗ : ∃t ∈ E ∗ st ∈ L} .

L = {a, bg, gba} E = {a, b, g} L L = {ε, a,
L = {a, bg, gba} E = {a, b, g}
L
L = {ε, a, b, bg, g, gb, gba} .

L

¯

L

E ∗ : ∃t ∈ E ∗ st ∈ L} . L = {a, bg, gba}

L E L

L =

i=0

L n ,

L 0

=

{ε} ,

L i

=

L i1 L.

L ∗ L ∗ = ∞ i =0 L n , L 0 = { ε

L = {a, bg, gba} E = {a, b, g} L

L =

i=0

L n ,

L 0

=

{ε} ,

L 1

=

L 0 L = {a, bg, gba} ,

L 2

=

L 1 L = {a, bg, gba} {a, bg, gba} = {aa, abg, agba,

gbabg,

.} ,

a, bg, gba } , L 2 = L 1 L = { a, bg, gba

{a} ∪ {b} = {a, b}

{ab} ⊆ {a} ∪ {b}

{a} ∪ {a, b} = {a, b}

abb ∈ {a} {a, b}

L 1 L 2 L 2 L 1 L 1 = L 2

a, b } ∗ = { a, b } ∗ abb ∈ { a } {

ε / {ε} ε

L = L = L

= {ε} {ε} = {ε}

= ε L

u

= {u}

u

v = {u, v} = {u} ∪ {v}

u = {ε, u, uu, uuu, uv = {u}{v}

}

∈ L u = { u } u ⊕ v = { u, v } =

ε e E E

p q pq qp p q p q

∅ ε e ∈ E E p q pq qp p ∗ q ∗ p ⊕

L 1 = a (a b)

L 2 = a i b i , i N a i b i a b i

L 1 = a ( a ⊕ b ) ∗ L 2 = a i b

L M N E

L = M N L = ML

ε / M L = ML

N

N L = M N

ε / M L = M N

L = ML

X = AX B

N

ε ∈ / M L = ML ⊕ N N L = M ∗ N ε

G

L m (G) = {s E : f(x 0 , s) X m }

L x i = {s E : f(x i , s) X m }

x i

∗ : f ( x 0 , s ) ∈ X m } L x i

G L x L y L z x y z

a b a x y g a, g z
a
b
a
x
y
g
a, g
z

b

G L x L y L z x y z a b a x y g

L

L

L

x

y

z

= aL ⊕ gL z ⊕ ε, x = aL ⊕ bL y , x
=
aL
⊕ gL z ⊕ ε,
x
=
aL
bL y ,
x
=
(a ⊕ g) L y ⊕ bL z ⊕ ε.
a
b
a
x
y
g
a, g
z

b

L x y z = aL ⊕ gL z ⊕ ε, x = aL ⊕ bL

L y = b aL x .

a b a x y g a, g z
a
b
a
x
y
g
a, g
z

b

L y = b ∗ aL x . a b a x y g a, g

L z = b [(a g) L y ε] .

a b a x y g a, g z
a
b
a
x
y
g
a, g
z

b

L z = b ∗ [( a ⊕ g ) L y ⊕ ε ] .

L z = b [(a g) b aL x ε]

a b a x y g a, g z
a
b
a
x
y
g
a, g
z

b

L z = b ∗ [( a ⊕ g ) b ∗ aL x ⊕ ε

L x = aL x gb [(a g) b aL x ε] ε.

a b a x y g a, g z
a
b
a
x
y
g
a, g
z

b

L x = aL x ⊕ gb ∗ [( a ⊕ g ) b ∗ aL

G

L x = L m (G) = [a gb (a g) b a] (gb ε) .

a b a x y g a, g z
a
b
a
x
y
g
a, g
z

b

( G ) = [ a ⊕ gb ∗ ( a ⊕ g ) b ∗

G 1 G 2

L (G 1 )

=

L (G 2 ) ,

L m (G 1 )

=

L m (G 2 ) .

1 G 2 L ( G 1 ) = L ( G 2 ) , L

G = (X, E, f, Γ, x 0 , X m )

x m X m

x nm X \ X m

x 1 , x 2 X f (x 1 , e) f (x 2 , e) e E x 1 x 2

x 1 , x 2 X e E

f (x 1 , e) = f (x 2 , e)

f (x 1 , e) = x 2

f (x 2 , e) = x 1

∈ E f ( x 1 , e ) = f ( x 2 , e

E = {a, b} b x x 1 2 a b a, b a, b
E = {a, b}
b
x
x
1
2
a
b
a, b
a, b
x 3
x
4
a

x

x

x

3

2

1

 

x 4

x 3

x 2

x 1
x
1

b

x 2
x
2

a

b
b

a, b

 

a, b

a, b
x 3
x 3
x 3 x 4
x 4
x
4

a

x x x 3 2 1   x 4 x 3 x 2 x 1 b

x 1

x 2 x 3

x 4

x 3 x 2 x 1 x 4 x 3 x 2 b x x
x
3
x
2
x
1
x 4
x 3
x 2
b
x
x
1
2
a
b
a, b
a, b
x 3
x
4

a

x 1 x 2 x 3 x 4 x 3 x 2 x 1 x 4

x 2 x 3 e = a, b

f (x, e) = x 4

x = x 2 , x 3

x 3 x 2 x 1 x 4 x 3 x 2 b x 1
x
3
x
2
x
1
x 4
x 3
x 2
b
x 1
x
2
a
b
a, b
a, b
x 3
x
4

a

a, b f ( x, e ) = x 4 x = x 2 , x

x 2 x 4 f (x 2 , a) = x 4

f (x 4 , a) = x 3 = x 2 f (x 2 , b) = x 4 f (x 4 , b) = x 2

x 3

x 2 x 1 x 4 x 3 x 2 b x 1 x 2
x 2
x 1
x 4
x 3
x 2
b
x 1
x
2
a
b
a, b
a, b
x 3
x
4

a

, b ) = x 4 f ( x 4 , b ) = x 2

x 3 x 4 f (x 3 , a) = x 4

f (x 4 , a) = x 3 f (x 3 , b) = x 4 f (x 4 , b) = x 2 = x 3

x 3 x 2 x 1 x 4 x 3 x 2 b x 1
x 3
x 2
x 1
x 4
x 3
x 2
b
x 1
x
2
a
b
a, b
a, b
x 3
x
4

a

x 4 f ( x 4 , b ) = x 2 = x 3 x

L m (G) = L (G) .

L m ( G ) = L ( G ) .

aa ∈ L (G)

aa / L m (G) L m (G)

= L (G)

a x y b a z
a
x
y
b
a
z

aa ∈ L ( G ) aa ∈ / L m ( G ) L m

G = (X, E, f, Γ, x 0 , X m )

e E

e x 1 e x x 0 2 e x n
e
x
1
e
x
x
0
2
e
x
n
G = ( X, E, f, Γ , x 0 , X m ) e ∈

G ND = (X, E∪ {ε}, f ND , Γ, x 0 , X m )

X

E

f ND

f ND : X × E∪{ε} 2 X

Γ Γ : X 2 E{ε}

x 0

X m

x 0 X

X m X

2 X Γ Γ : X → 2 E ∪ { ε } x 0 X

a a x 1 x 2 b
a
a
x
1
x 2
b

a a x 1 x 2 b

X = {x 1 , x 2 } , E = {a, b} , a
X
=
{x 1 , x 2 } ,
E
=
{a, b} ,
a
a
x
1
x 2
b

X = {x 1 , x 2 } , E = {a, b} , a a

f ND (x 1 , a)

=

{x 1 , x 2 } ,

f ND (x 2 , b)

=

{x 1 } ,

Γ (x 1 )

=

{a} ,

Γ (x 2 )

=

{b} ,

a a x x 1 2 b
a
a
x
x
1
2
b
, b ) = { x 1 } , Γ ( x 1 ) = {

x 0 = X m = x 1 , {x 1 } . a a
x 0
=
X m
=
x 1 ,
{x 1 } .
a
a
x 1
x
2
b

x 0 = X m = x 1 , {x 1 } . a a x

2 X

2 X

a a x 1 x 2 b
a
a
x
1
x 2
b

a a x 1 x 2 b

2 X

X

=

{x 1 , x 2 }

,

2 X

=

{∅, {x 1 } , {x 2 } , {x 1 , x 2 }} .

a a x x 1 2 b
a
a
x
x
1
2
b

, x 2 } , 2 X = {∅ , { x 1 } , {

2 X

f ({x 1 } , a) = {x 1 , x 2 } , f
f ({x 1 } , a)
=
{x 1 , x 2 }
,
f
({x 1 , x 2 } , a)
=
{x 1 , x 2 }
,
f
({x 1 , x 2 } , b)
=
{x 1 } .
a
a
x
x
1
2
b

x 0 = {x 1 } X m

X m = x 2 X : x x x X m ,

X m = {{x 1 } , {x 1 , x 2 }} .

a a x x 1 2 b
a
a
x
x
1
2
b

: ∀ x ∈ x ∃ x ∈ X m , X m = {{ x

a

a x x 1 2 b a a {x } {x , x } 1
a
x
x
1
2
b
a
a
{x
}
{x
, x
}
1
1
2
b
a a x x 1 2 b a a {x } {x , x } 1

ε

ε

ε

ε ε ε

ε

a b ε x 1 x 2
a
b
ε
x 1
x 2

ε a b ε x 1 x 2

ε

X = {x 1 , x 2 } , E = {a, b} , a
X
=
{x 1 , x 2 } ,
E
=
{a, b} ,
a
b
ε
x 1
x 2

ε X = {x 1 , x 2 } , E = {a, b} , a